Stress testing and myocardial perfusion imaging for patients after recovery from severe COVID-19 infection requiring hospitalization: A single-center experience - Hasnie, Usman A. (J Nucl Cardiol, 2021)
BACKGROUND: As the coronavirus pandemic progresses, patients that have recovered from COVID-19-related hospitalization require resumption of care for other medical issues. Thus far, the literature has not detailed the experience of stress testing in this patient population. METHODS: We retrospectively reviewed patients that recovered from COVID-19-related hospitalizations and underwent SPECT MPI studies at the University of Alabama at Birmingham Medical Center. RESULTS: 15 patients (median age 60 years, 67% male) were identified with COVID-19-related hospitalization and then underwent SPECT MPI imaging after recovery. During COVID-19-related hospitalization (median length of stay 8 days), patients received various COVID-19 therapies; 3 required mechanical ventilation. Stress tests (4 Exercise, 11 Pharmacologic) were performed 65 days (interquartile range 31-94 days) after the diagnosis of COVID-19. None of the patients experienced serious adverse events during or after stress testing. One patient required regadenoson reversal using aminophylline due to chest pain. CONCLUSION: Over time, more patients that recover from COVID-19 infection will require MPI testing for myocardial ischemia evaluation. Our study provides some information regarding performing stress testing in patients who have recently recovered from COVID-19 infections requiring hospitalization. Further studies are recommended to establish formal protocols for testing in this cohort. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12350-021-02606-w.